Leptospirosis in humans and animals in Malaysia: A review from 1976 to 2023 - Joy Siang Xin Lea; Mohd Farhan Hanif Reduan; Siew Shean Choong; Intan Noor Aina Kamaruzaman; Peck Toung Ooi; Sazaly AbuBakar; Shih Keng Loong; Mohammad Sabri Abdul Rahman (Veterinary World)
Leptospirosis is a globally distributed zoonotic disease that remains under-reported and misdiagnosed, particularly in tropical regions such as Malaysia. This review provides a comprehensive analysis of leptospirosis cases in humans and animals in Malaysia from 1976 to 2023, examining trends in prevalence, outbreak patterns, diagnostic advancements, and associated risk factors. The disease is primarily transmitted through direct contact with infected animals or indirectly via contaminated water and soil, with rodents serving as a major reservoir. In Malaysia, leptospirosis prevalence has increased in recent years, with a notable correlation between outbreaks and occupational exposure, recreational water activities, and monsoon-related flooding. Surveillance data indicate that specific populations, including agricultural workers, town service employees, and animal handlers, are at elevated risk. Furthermore, the disease is commonly misdiagnosed due to its clinical similarities with other endemic febrile illnesses, such as dengue fever and malaria. Advances in diagnostic methodologies, particularly the increasing use of molecular techniques such as polymerase chain reaction (PCR), have enhanced early detection, although serological tests remain widely used in epidemiological studies. This review underscores the necessity of a One Health approach, integrating human, animal, and environmental health strategies to improve surveillance and control measures. Future research should focus on strengthening diagnostic capabilities, understanding environmental reservoirs, and implementing targeted public health interventions to mitigate leptospirosis transmission in Malaysia.